Development of a nutrient‐dense complementary food using amaranth‐sorghum grains - Okoth, Judith Kanensi (Food Sci Nutr, 2016)
Thin porridge from cereals and starchy tubers is a common complementary food in Sub Saharan Africa. It may be high in antinutrients, low in energy, and nutrient density hence inadequate in providing infants' high energy and nutrients requirements per unit body weight. Consequently, undernourishment levels among children under 5 years are high. Therefore, there is need to avail nutrient‐dense complementary foods especially for children in low‐resource settings. The study was aimed at developing a nutrient‐dense complementary food from amaranth and sorghum grains. Amaranth grain, a pseudocereal, though rarely used as a complementary food in Kenya has a higher nutritional quality than other staples. Plant‐based foods are known to have high levels of antinutrients. Steeping and germination were used to reduce the levels of antinutrients and enhance the bioavailability of minerals in the grains. Various steeped and germinated amaranth and sorghum grains formulations were made to find the ratio with the highest nutrient content and lowest antinutrient levels. The 90% amaranth‐sorghum grains formulation had significantly (F = 32.133, P < 0.05) higher energy (5 kcal per g on dry weight basis) than the other formulations and a protein content of 14.4%. This is higher than the estimated protein needs from complementary foods even for a 12–23 months child of low breast milk intake (9.1 g/d). Antinutrients could not be detected which could imply enhanced nutrient bioavailability. Therefore, a nutrient‐dense complementary food product was developed from steeped and germinated amaranth and sorghum grains with 90% amaranth grain. In ready to eat form, it would give an energy content of 1.7 kcal per g (dilution of 1:2 amaranth‐sorghum flour to water) and 1.2 kcal per g (dilution of 1:4 amaranth‐sorghum flour to water). It can be used as a nutrient‐dense complementary food and for other vulnerable groups.